TGFA/Taq I polymorphism and environmental factors in non-syndromic oral clefts in Southern Brazil - Liliane Todeschini de Souza; Thayne Woycinck Kowalski; Ana Paula Vanz; Roberto Giugliani; Têmis Maria Félix (Sociedade Brasileira de Pesquisa Odontológica, 2012)
We report a study of TGFA/ Taq I polymorphisms and environmental factors in non-syndromic oral cleft in Southern Brazil. Nonsyndromic cleft case-parent triads were recruited to participate. Clinical data was collected with an emphasis on tobacco and alcohol use during pregnancy. DNA was extracted from peripheral blood and TGFA/ Taq I polymorphisms were analyzed by PCR/RFLP with Taq I restriction enzyme. Association of clefts and TGFA/ Taq I polymorphisms was determined using a transmission disequilibrium test (TDT). Association of environmental factors, clefts, and genotypes was evaluated with Fisher's exact test. The minor allele frequency was 0.064. We found no evidence of association between TGFA/ Taq I polymorphisms and clefting (TDT p = 0.335). We also found no association between TGFA/ TaqI polymorphisms and environmental factors (alcohol and/or tobacco). Therefore, no evidence was found that TGFA/ Taq I polymorphisms play a role in clefting in this population. No evidence was found that tobacco or alcohol exposure during pregnancy was related to clefting, however a larger sample size is needed to confirm these results.